Immediate impacts of COVID-19 measures on bean production, distribution, and food security in eastern Africa - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu; Karanja, David (Lyson Center for Civic Agriculture and Food Systems, 2021)
The outbreak of coronavirus was expected to adversely affect African countries more than any other region in the world. This assertion was based on the existing conditions in sub-Saharan Africa that exposed the region to the dire consequences of the pandemic. Previously existing underlying conditions that affected the food system include a high dependence on trade for inputs supply, the adverse effects of climate change, crop pests and diseases, poverty, low input use, weak institutions and ineffective policies, and insecurity and conflicts. We collected data from farmers, aggregators, bean research coordinators, and urban and peri-urban consumers in five Eastern African countries in order to describe the immediate impacts of the pandemic on the bean value chain. Access to seed and labor appear to be the most critical impacts of the pandemic on bean production. There are observable differences in patterns and frequency of bean consumption in these regions, suggesting that the effect of the pandemic depends on the level of implementation of containment measures and pre–COVID-19 underlying conditions that affect the food systems. In the mid to long-term, the pandemic may disrupt food systems, resulting in hunger, malnutrition, and food insecurity. Thus, governments should support farmers and businesses in becoming resilient to exogenous shocks through increased efficiency in supply chains, capacity building, and the adoption of modern digital technology.